Economic Empowerment of Impoverished IPV Survivors: A Review of Best Practice Literature and Implications for Policy. (April 2014) - Hahn, Sur Ah; Postmus, Judy L.
Best practices in advocating for economic empowerment of impoverished intimate partner violence (IPV) survivors require the comprehensive and holistic organization of program and service delivery systems. This article outlines the best practices literature that addresses IPV in the lives of impoverished women, as well as the literature that specifically examines the interventions to economically empower IPV survivors—whether impoverished or not. This article concludes with suggestions for policy makers on how to incorporate these best practices into the Violence Against Women Act and for practitioners to ensure a comprehensive approach to interventions for impoverished IPV survivors.